The Effectiveness of Holistic Homeopathy in the Treatment of Uterine Fibroids (Homoeopathy for All, 2024)
As a homoeopathic physician comes across gynecological and  obstetrical problem daily so in this  we will describe a group of remedies  which help in treatment for the cases  of Uterine Fibroids.
Keywords: Homoeopathic rem edies; Tumors; Uterine Fibroids etc